Tagging active neurons by soma-targeted Cal-Light - Jung Ho Hyun; Kenichiro Nagahama; Ho Namkung; Neymi Mignocchi; Seung-Eon Roh; Patrick Hannan; Sarah Krüssel; Chuljung Kwak; Abigail McElroy; Bian Liu; Mingguang Cui; Seunghwan Lee; et al. (Nature Communications, 2022)
Techniques for tagging active neurons with high spatiotemporal precision are limited. Here the authors report soma-targeted CalLight (ST-Cal-Light) which selectively converts somatic calcium rise triggered by action potentials into gene expression, and generate a conditional ST-Cal-Light knock-in mouse.